Rozie Times: 100 days with Rozie / Galeri Seni Tuanku Nur Zahirah - UiTM, Galeri Seni Tuanku Nur Zahirah (GESTURZ) (Galeri Seni Tuanku Nur Zahirah (GESTURZ), 2021)
Rozie Times celebrates the first 100 days in office for UiTM Vice-Chancellor, Professor Ts Dr Roziah Mohd Janor, fondly known as Rozie. Featuring a collection of posts that appeared in the Vice-Chancellor's Official Facebook page, Rozie Times is a creative idea from the Vice-Chancellor inspired by the newspaper concept in which the anatomy and key design elements of a newspaper have been adopted.